An Analysis of Envelope of Pile-Soil Interaction of OWT in Layered Soils - Zhen Huang, Meng Jiang (Forest Chemicals Review, 1970)
In recent years, with the increase of energy demand and the need of environmental protection, offshore wind turbines (OWTs) are gradually used in offshore and deep water and single pile foundation is the most common foundation form. But with the increase of the depth, combined with complex load combination such as wind, wave and flow, and with the increase of buried depth, the soil property around pile foundation becomes more complex and changeable. Therefore, the research on the bearing capacity of OWT with super-large diameter foundation has become an important issue. In this paper, FEM is adopted with ABAQUS, and the model of pile and layered soil is set to analysis the ultimate bearing capacity in single load, and the envelope for horizontal and vertical load. In addition, the strength of soil is considered as an affecting factor to analysis the related response.